Physical-chemical and sensory evaluation of cookie made with potato (Solanum Tuberosum L.) and beet (Beta Vulgaris L.) Mixed flour (Research, Society and Development, 2020)
This study aimed to develop a cookie from the mixed flour derived from dehydrated pulp of beet and potatoes, by drying in a tray dryer and assessing their physical-chemical and sensory characteristics. Three formulations were prepared: Standard (0%), Type I (10%) and Type II (20%). The percentage correspond to the mixed flour added to the basic formulation. The data of the flour drying process showed a moisture loss of the potatoes and beet around 83.5 and 86.2%, respectively. The Type I and II cookies had an average chemical composition respective 0.3 to 0.7% moisture, 70% carbohydrates for both, 5 and 7% protein, 22 and 20% fat and 2% minerals for both, with an average calorific value of 505 and 491 kcal x 100 g-1. All formulations showed satisfactory acceptance through sensory analysis, and there was no statistical difference between the types of cookie for all attributes. The model Midilli describes the drying kinetics with a good parameter of fit. So, this product is very promising, taking into account the range of additional nutrients from the raw materials (mainly minerals), calorific value similar to those found on Brazilian market and consumer acceptance, besides the possibility of use as a coloring agent.